YURISDIKSI INTERNATIONAL CRIMINAL COURT TERHADAP KEJAHATAN LINGKUNGAN HIDUP - Ardhiansyah, Agis; Akbar Aprilia Ardhiansyah (PERSPEKTIF : Kajian Masalah Hukum dan Pembangunan, 2024)
The jurisdiction of the International Criminal Court (ICC) over environmental crimes has become a critical issue in international criminal law, particularly concerning the potential recognition of ecocide as an international crime. Although the Rome Statute does not yet formally include ecocide within its scope, discourse surrounding its inclusion has intensified amid the worsening global environmental crisis. This study employs a normative legal approach to examine the development of international legal norms relating to environmental crimes and to evaluate the feasibility of expanding the ICC’s jurisdiction to encompass ecocide. The findings indicate that the inclusion of ecocide under the ICC’s jurisdiction could enhance global environmental protection and reduce impunity for those responsible for severe environmental harm. However, normative and practical challenges—such as the formulation of a clear legal definition and the establishment of constitutive elements of the crime—remain significant obstacles to implementation. This research contributes to the advancement of international legal discourse on environmental protection and accountability for environmental crimes.